Effect Of Supplementation On Haematological And Biochemical Parameters During Pregnancy - Mohapatra P; Mohapatra S.C; Agarwal D.K; Agarwal K.N (Wolters Kluwer Medknow Publications, 1988)
One hundred forty eight antenatal women were studied as supplemented (70) and non-supplemented (78) groups. The former group received nutritional supplementation in addition, to Iron, Folic acid and calcium tablets, which were given to both the groups. There was significant increase in the serum protein (p<0.001) and albumin (p<0.001) levels of the supplemented women. Haemoglobin was found to be increased in both the groups because of Iron therapy. But the increment was significantly higher (p<0.001) in supplemented group. Thus apart from Iron and Folic Acid, a diet rich in proteins (11 gm) with calories (330 kcal) is essential during pregnancy, at least for a period of 100 days.